WEBBED MODEL INTEGRATED LEARNING ON PROBLEM SOLVING AND SELF- REGULATION SKILLS FOR PAUD STUDENT IN MOJOKERTO - Sutik, Sutik; Masitoh, Prof. Dr. Siti; Mariono, Dr. Andi (jfpublisher, 2022)
Early Childhood Education or commonly called PAUD is one of the formal educational institutions that presented at the pre-school level or before students register in kindergarten. This education presents activities that provide more and intense touch and affection, generally because at this time children have entered the